PENYELENGGARAAN PELAYANAN KELUARGA BERENCANA DALAM JAMINAN KESEHATAN NASIONAL - Oktriyanto, Oktriyanto (Jurnal Ilmu Keluarga dan Konsumen, 2016)
The National Health Insurance Program was organized with the aim that each participant obtain maintenance and protection in fulfilling the basic needs of health, including family planning services. The purpose of this study is to describe the implementation of family planning services in The National Health Insurance Program. This study used cross sectional design. The respondents of this study are from family, institutions and family planning service providers in the Province of Lampung (Bandar Lampung and Pesawaran), West Java (Bandung and Purwakarta), Central Kalimantan (Palangkaraya and Pulang Pisau), and East Nusa Tenggara (Kupang city and Kupang district). Respondent of familiy involve 240 women of couples of childbearing age (PUS); which is involved 30 people in each study site. Generally, the result showed that the readiness of institutions in implementation of the family planning services in the national health insurance were not maximized, health facility information system between BKKBN and BPJS Kesehatan (Healthcare and Social Security Agency) had not been integrated, and the community's knowledge about The National Health Insurance Program was relative high, but BPJS Kesehatan (Healthcare and Social Security Agency) card ownership was still low.